Psychological factors affecting the participation of pregnant women in physical activities in Uganda - Nakazibwe, Winfred (2016)
Winfred Nakazibwe, 2016. A qualitative research, exploring the psychological factors affecting the participation of pregnant women in physical activities in Uganda. University of Jyvaskyla. 97 pages.